Menara AmFirst, Petaling Jaya / Mohd aizat Aizani Yusof ... [et al.] - Mohd aizat, Aizani Yusof; Muhammad Afiq Amirnuddin, Ependy; Siti Sarah, Mohd Nasron; Husna Athirah, Roslan; Nurul Nashatul Aina, Mohd Razi (2019)
As final year student, students are required to prepare a report about Integrated Final Project (IFP). For this report, a group of students are required to find one case study building in Malaysia. Students are required to study and analyse the data about the maintenance of the building and its organization. This report consists of 9 chapters that discussing important parts and information according to the chapter which is The details of property, Maintenance team organization, responsibilities and scope of work in organizational maintenance management, Maintenance Policy, Planning and Programme discussing the maintenance schedule and programme, Building design and technology discussing the building's design meaning and specification of materials used in the building, Building audit survey are carried out in Building condition assessment to inspect the condition of the building, Maintenance strategy consists of maintenance strategy are being implemented in the building, Legal aspect refer to law and regulation related to the building such as Uniform Building by Law (UBBL 1984), Street, Drainage and Building 197 4 (Act 133). Occupational Safety and Health 1994 (OSHA) and Electrical Supply Act 1990 (Act 447)m, In Financial/ Maintenance budget forecast included the information of income and expenditure and also budget forecasting for future years. Last but not least all the obtain information are analyse and extracted to find the strength and weakness of the building maintenance and students are required to make recommendation and suggestion towards the issues. Summary for all the chapters are also provided to conclude the chapter.